MENJEMBATANI DIKOTOMI ILMU AGAMA DAN ILMU UMUM (KAJIAN ATAS PEMIKIRAN INTEGRATIF M. AMIN ABDULLAH) - Saputra, Adi; suyanta, sri (LPPM STAI Muhammadiyah Probolinggo, 2025)
The long-standing dichotomy between religious sciences and general sciences has created a significant epistemological gap that affects the development and relevance of Islamic education in the modern era. This article aims to comprehensively analyze M. Amin Abdullah’s integrative–interconnective paradigm as an alternative approach to bridging this separation and constructing a more holistic scientific framework. Using a literature-based method, this study examines the conceptual foundation, epistemological principles, and practical implications of an integrative model that harmonizes revelation, reason, and empirical reality. The findings indicate that Amin Abdullah’s “spider web of knowledge” encourages multidisciplinary, interdisciplinary, and transdisciplinary dialogue, thereby overcoming fragmentation and generating mutually reinforcing scientific insights. These results demonstrate that the integrative–interconnective paradigm is not only a theoretical framework for reconstructing contemporary Islamic epistemology but also has substantial implications for curriculum reform, learning strategies, character development, and the strengthening of religious moderation. Thus, this approach provides a significant contribution to shaping Islamic education that is more responsive, adaptive, and relevant to the challenges of the digital age and the complexities of modern life.